HUBUNGAN FASILITAS BELAJAR DENGAN MOTIVASI BELAJAR SANTRI DI TPQ MASJID AL-KAUTSAR PERUMAHAN BUNGO BUMI INDAH KELURAHAN BUNGO PASANG KECAMATAN KOTO TANGAH KOTA PADANG - ilham, ilham (Ruhama : Islamic Education Journal, 2019)
This research departs from researcher observation at TPQ Masjid Al-Kautsar Bungo Bumi Indah Estate Bungo Pasang Subdistrict Koto Tangah Subdistrict Padang City. Researchers found various problems, such as: 1) learning facilities, classrooms for learning santri already inadequate. 2) Variations in the santri learning schedule. The formulation of the problem in this research are: 1) How is the description of student learning facilities at TPQ Masjid Al-Kautsar. 2) How to describe the motivation to learn santri in TPQ Masjid Al-Kautsar. 3) Is there a significant relationship between study facilities with the motivation to learn santri at TPQ Al-Kautsar Mosque. Aim. 1) To know the condition of learning facilities at TPQ Masjid Al-Kautsar. 2) To know the description of students' motivation in TPQ Masjid Al-Kautsar. 3) To find the relationship between learning facilities with the motivation to learn santri at TPQ Masjid Al-Kautsar Bungo Bumi Indah Housing Bungo Pasang Subdistrict Koto Tangah Subdistrict Padang City.